Modification and stabilization of Malaysian cohesive soils with lime - Kassim, Khairul Anuar (Southeast Asian Geotechnical Society, 2005)
Lime mix with cohesive soil has a pronounce effect on its physical and chemical properties. The soil modifies as soon as lime is mixed by changing its plasticity characteristics and particle size through cation exchange and flocculation. Stabilization on the other hand is a process which took place in a later stage after modification depending on the available lime content, mineralogy, microstructure properties and alkaline environment of the soil. The alkaline environment is essential in making the silicates and aluminates become soluble for the soil-lime reaction to take place. New cementitious compounds that crystallized with age were detected through SEM and XRD. The crystallized gels known as calcium silicate hydrate and calcium aluminate hydrate bind the soil particles thus increasing the shear strength of the soil. The strength development based on the microstructure and mineralogy aspects were studied. Tests conducted which include basic characteristics tests on soil and lime, compressive strength test, chemical tests and microstructure identification have provided the inside mechanism of soil-lime reactions and a clear understanding of lime modification and stabilization processes.